Pedagogical-psychological and rehabilitation activities carried out in forensic mental health units - Piątek, Karolina (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
Mental disorders are a very common group of disorders. They limit a person’s ability to perform social roles and cause various reactions of the society. They are very common, even in highly developed countries. They are also highly excluding illnesses. The research shows that today’s civilization is not free from stereotypes regarding mental disorders. Pedagogical-psychological and rehabilitation practices among patients in forensic mental health units should be effective. The author presents the types of activities addressed to inpatients of these detention wards in psychiatric hospitals.